2017
DOI: 10.1038/s41598-017-14208-z
|View full text |Cite
|
Sign up to set email alerts
|

HtrA1 activation is driven by an allosteric mechanism of inter-monomer communication

Abstract: The human protease family HtrA is responsible for preventing protein misfolding and mislocalization, and a key player in several cellular processes. Among these, HtrA1 is implicated in several cancers, cerebrovascular disease and age-related macular degeneration. Currently, HtrA1 activation is not fully characterized and relevant for drug-targeting this protease. Our work provides a mechanistic step-by-step description of HtrA1 activation and regulation. We report that the HtrA1 trimer is regulated by an allos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…In line with these observations, deletion of the trimerization motif in human HtrA2 showed that the formation of the homotrimer is essential for precise function of the enzyme including its proteolytic activity ( Li et al, 2002 ; Nam et al, 2006 ). Recently, it was experimentally also shown that trimerization plays a fundamental role for the activation of human HtrA1 by an allosteric mechanism ( Cabrera et al, 2017 ). Further, computational studies of DegS suggest that disassembly of a DegS trimer inhibits proteolytic activity ( Lu et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…In line with these observations, deletion of the trimerization motif in human HtrA2 showed that the formation of the homotrimer is essential for precise function of the enzyme including its proteolytic activity ( Li et al, 2002 ; Nam et al, 2006 ). Recently, it was experimentally also shown that trimerization plays a fundamental role for the activation of human HtrA1 by an allosteric mechanism ( Cabrera et al, 2017 ). Further, computational studies of DegS suggest that disassembly of a DegS trimer inhibits proteolytic activity ( Lu et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among the other missense HTRA1s observed in the symptomatic carriers, four of the five missense HTRA1s had a mutation in the LD domain. The simulation analysis revealed that these mutations induced an instability in the helical structure of the LD loop (16). For the L3 domain, R302 is the only portion observed in the symptomatic carrier.…”
Section: Discussionmentioning
confidence: 99%
“…For the L3 domain, R302 is the only portion observed in the symptomatic carrier. R302 is essential for inter-monomer communication and substrate binding (16). Thus, a mutation in the LD or L3 domain that interferes with signal transduction between the monomers result in inhibition of the WT activity.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, two different mechanisms were proposed to underlie the dominant-negative effects of HTRA1 mutations (4,11): the inhibition of trimer formation, and the inhibition of the wild-type HTRA1 activity, observed in several missense mutations located in the sensor domain of loop 3 (L3) or the activation domain of loop D (LD) of HTRA1. These two domains play an essential role in the normal protease activity of HTRA1 (10,12). Among the previously reported missense mutations, p.R302 Q, which replaces the evolutionarily well-conserved arginine with glutamine, is the only mutation located in L3.…”
Section: Discussionmentioning
confidence: 99%